PERSEPSI PENGUNJUNG TERHADAP FASILITAS DI OBJEK WISATA PUNCAK ULU KASOK KABUPATEN KAMPAR - Ririn Wahyuningsih; Siti Sofro Sidiq (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research was conducted to determine the perception of visitors to the facilites ofa tourist attraction in Ulu Kasok Kampar District. This research is Quantitative Descriptive.The result of Visitors Perception To The Facility Of A Tourist Attraction In Ulu Kasok PeakKampar District categorized Good Enough with the average of value 8.407which is at skorrange 7.801-10.200. And the constrains in the management of facilities are funding theconstruction and addition of facilities, and less attention from the government.Keywords :Perception, Visitors, Facility, Tourist Attraction